TESTICULAR TORSION: CAUSATIVE FACTOR IN DELAYED MANAGEMENT - Abshari, Fatan; Wahyudi, Irfan; Rodjani, Arry (Indonesian Urological Association, 2018)
Objective: Analyzing the factors causing delays in the management of patients with testicular torsion in Dr. Cipto Mangunkusumo General Hospital Jakarta. Material & methods: This research is a retrospective research using questionnaire from patients as primary data and from Dr. Cipto Mangunkusumo General Hospital medical records or urologic reports as secondary data from 1st January 2011 to 30th April 2015. Results: 4 patients diagnosed with left testicular torsion admitted to hospital with >4 hours onset (as a prehospital factor). 3 of 4 patients were adult, who came with left testicle pain. The minimum VAS score perceived is 2. 3 of 4 patients had 540o medial left testicle rotation intraoperatively while all patients left testicles were unvital. Conclusion: Further examination is required to diagnose testicular torsion in adult-geriatric. Non-specific complaints, such as lower abdominal pain or painful testicles and mild pain in scrotum were some of the most important factors, thus causing delays in testicular torsion management. However, a comprehensive education to all health workers, especially for doctors is still required, because the complaints of pain in patients with testicular torsion does not always appear acutely. This becomes important for early identification of patients with testicular torsion, in order to prevent delay in management.